EU Citizenship and European Arrest Warrant: The Same Rights for All? - Marguery, Tony (Utrecht Journal of International and European Law, 2011)
In the case Wolzenburg, the principle of non-discrimination of European Union citizens is applied to the European arrest warrant. The implementation of the European arrest warrant by the Member States cannot escape a control of proportional- ity made by the Court. Member States may impose a period of residence of five years to foreign Europeans citizens in order for them to rely on an optional ground for non-execution of a European arrest warrant (Article 4(6) of the Framework Deci- sion on the European arrest warrant). Home nationals are not obliged to comply with a residence requirement. It is possible for Member States to justify an exception to the principle of non-discrimination of European citizens with a legitimate inter- est. The chances of social reintegration of a person convicted constitute such an interest. The national measure resulting in a difference of treatment must be proportional to that interest.